Section 150(1) Of The Insurance Act 1996 – Its Intended Application And A Case For Further Reform – - Hari Chand, Anil Joshi A/L (Journal of Malaysian and Comparative Law, 2019)
The enactment of the Insurance Act 1996 among other things resulted in the repeal of the Insurance Act 1963 and simultaneously introduced new laws regulating the insurance industry and the relationship between the insurer and the insured. This article will seek to show that though the enactment of our current section 150(1) must be commended, its full effect cannot be realised unless further reform is undertaken to provide alternative remedies in cases of innocent non-disclosure.